Jovian bow shock and magnetopause encounters by the Juno spacecraft. Issue 10 (25th May 2017) - Hospodarsky, G. B.; Kurth, W. S.; Bolton, S. J.; Allegrini, F.; Clark, G. B.; Connerney, J. E. P.; Ebert, R. W.; Haggerty, D. K.; Levin, S.; McComas, D. J.; Paranicas, C.; Rymer, A. M.; et al.
Abstract: The Juno spacecraft has crossed Jupiter's bow shock (BS) and magnetopause (MP) multiple times in the dawn sector (near 0600 local time), both during the approach to Jupiter and during the first three apojove periods. A survey of all of these crossings using the Juno field and particle instruments has been performed, with 51 bow shock and 97 magnetopause crossings being detected. The BS crossings ranged from 92 to 128 R J with 1 encounter during the approach, 36 during the first apojove period, 0 on the second, and 14 during the third. The MP crossings ranged from 73 to 114 R J, with 8 MP encounters during the approach, 40 encounters during the first apojove period, 24 encounters on the second, and 46 during the third. During the approach, Juno initially encountered an expanding magnetosphere resulting in a single BS and MP crossing, followed a few days later by a contracting magnetosphere, resulting in 7 more MP crossings and a BS crossing on the first outbound orbit at 92 R J . The lack of BS crossings and the limited number of MP crossings during the second apojove period suggests a long period of an expanded magnetosphere, likely caused by a prolonged period of low solar wind dynamic pressure associated with a rarefaction region. The detection of BS crossings on the third apojove period suggests another period of a highly compressed magnetosphere. Key Points: Multiple bow shock and magnetopause crossings provide important information on the size and dynamics of the magnetosphere Variations in the number of crossings encountered and their location suggest a dynamic solar wind and magnetosphere interaction Multiple bow shock crossings separated by only few minutes suggest either a highly variable solar wind or large‐scale variation in the flank region